2013
DOI: 10.1111/anu.12091
|View full text |Cite
|
Sign up to set email alerts
|

A review on broodstock nutrition of marine pelagic spawners: the curious case of the freshwater eels (Anguillaspp.)

Abstract: To sustain eel aquaculture, development of reproduction in captivity is vital. The aim of this review is to assess our current knowledge on the nutrition of broodstock eels in order to improve the quality of broodstock under farming conditions, drawing information from wild adult eels and other marine pelagic spawners. Freshwater eels spawn marine pelagic eggs with an oil droplet (type II), and with a large perivitelline space. Compared with other marine fish eggs, eel eggs are at the extreme end of the spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 239 publications
(344 reference statements)
2
13
1
1
Order By: Relevance
“…5000 km spawning migration from Europe to arrive 6 to 7 months later at their spawning site, which is presumed to be in the Sargasso Sea (Schmidt, 1922;Tesch, 2003). In this regard, the development of 'optimal' broodstock diets may improve the species' reproductive success in captivity, through the production of highquality gametes and viable offspring from farmed fish (Heinsbroek et al, 2013;Støttrup et al, 2013). After studying sperm quality parameters and fatty acid composition during hormone-induced sexual maturation, Baeza et al (2014) found significant correlations between several fatty acids and sperm quality parameters in male European eel.…”
Section: Introductionmentioning
confidence: 99%
“…5000 km spawning migration from Europe to arrive 6 to 7 months later at their spawning site, which is presumed to be in the Sargasso Sea (Schmidt, 1922;Tesch, 2003). In this regard, the development of 'optimal' broodstock diets may improve the species' reproductive success in captivity, through the production of highquality gametes and viable offspring from farmed fish (Heinsbroek et al, 2013;Støttrup et al, 2013). After studying sperm quality parameters and fatty acid composition during hormone-induced sexual maturation, Baeza et al (2014) found significant correlations between several fatty acids and sperm quality parameters in male European eel.…”
Section: Introductionmentioning
confidence: 99%
“…, ; Heinsbroek et al . ). The results from the present study show a strong influence of the dietary fatty acid composition on fatty acid composition of European eel eggs, both in neutral lipids and in phospholipids.…”
Section: Discussionmentioning
confidence: 97%
“…Two experimental diets were developed, based on available knowledge on nutrient requirements (NRC ; Heinsbroek et al . ) and from a comparison of fatty acid content in the muscle and ovaries of wild‐caught and farmed female eel. These diets were tested against a commercial eel feed.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have proven the importance of broodstock nutrition in the reproductive performance of fish (Asturiano, 1999;Bobe and Labbé, 2010;Glencross, 2009;Heinsbroek et al, 2013;Izquierdo et al, 2001;Watanabe and VasalloAgius, 2003). The development of optimum diets for European eel broodstocks to ensure high quality gametes is key if we want to improve the chances of reproduction in captivity.…”
Section: Introductionmentioning
confidence: 99%
“…In order for eel aquaculture to be sustainable, the life cycle should be completed in captivity. In this regard, the development of 'optimal' broodstock diets may improve the species' reproductive success in captivity, through the production of high-quality gametes and viable offspring from farmed fish (Heinsbroek et al, 2013;Støttrup et al, 2013). After studying sperm quality parameters and fatty acid composition during hormoneinduced sexual maturation, Baeza et al (2013;Chapter III) found significant correlations between several fatty acids and sperm quality parameters in male European eel.…”
Section: Introductionmentioning
confidence: 99%